Desenvolvimento de genossensores utilizando microbalança de cristal de quartzo e técnicas eletroquímicas - Pedroso, Mariele Mucio (2011)
The proliferation of toxic algae in different oceans leads to great economic losses and environmental damage the mortality of marine animals such as mollusks and fish due to neurotoxins that they release into the environment. The reasons that lead to algal blooms are not fully understood and thus the monitoring of algae is extremely important. In this sense, the genosensors appear as promising tools for the detection of toxic algal blooms in coastal waters, as they offer the possibility of in situ detection with high sensitivity and selectivity. In this project we studied the processes of hybridization of DNA molecules without the use of marker molecules using electrochemical and microgravimetric techniques. Probes were used as partial sequences of primers of the gene encoding the ribosomal RNA sub-unit of the microalgae Alexandrium species. These species of algae produce neurotoxins that can accumulate in shellfish and are responsible for harm to human health. The probe DNA was immobilized by chemisorptions on the surface of a quartz crystal oscillating at 9 MHz third harmonic, 27 MHz. After the grounding of the probe, the crystals were exposed to target DNA molecules with sequence complementary to the probe and hybridization process was monitored in real time. The percentage of the crystal surface coverage and hybridization kinetics were monitored by quartz crystal microbalance (QCM). The area of the crystal suffered no links were filled with the reagent mercaptohexanol (MCH) and observed an improvement in the efficiency of hybridization. The cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used as a system for detection of DNA probe immobilization and hybridization with its complementary target, without the use of marker molecules. These events were monitored through changes in the electrical properties of the lead in media containing the redox couple [Fe(CN)6 3-/4-] before and after immobilization and hybridization. The analysis of xviii the impedance spectra showed an increase in Rct after the formation of doublestranded DNA, while the capacitance values remained unchanged after the modification of the electrode. The use of MCH during electrochemical measurements increased the efficiency of hybridization, in agreement with results obtained with the QCM technique. The technique of scanning electrochemical microscopy (SECM) was used to evaluate the charge transfer process before and after modifications to the DNA molecules. The results obtained with the SECM technique (approach curves) are qualitatively in agreement with results obtained by the techniques of QCM, CV and EIS with the redox couple [Fe(CN)6 3-/4-]. A microarray for DNA was constructed and evaluated, showing a good response in the detection of different nucleic acid sequences simultaneously. The genossensor developed allowed us to distinguish between targets and probes with different sequences, complementary and not complementary. A procedure for the regeneration of genossensor was developed and allowed the reuse of the DNA biosensor twenty times, with the same sensitivity.